2013
DOI: 10.1097/olq.0b013e31828b2f77
|View full text |Cite
|
Sign up to set email alerts
|

Biological Markers of Sexual Activity

Abstract: Research on interventions to prevent HIV and other sexually transmitted infections (STIs) is heavily influenced by participant reporting of sexual behavior, despite uncertainty about its validity. Exclusive reliance on participant self-report often is based, overtly or by implication, on 4 assumptions: (1) no feasible alternatives exist; (2) misreporting can be minimized to levels that can be disregarded; (3) misreporting tends to underreport sensitive behaviors; and (4) misreporting tends to be nondifferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
48
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 33 publications
3
48
1
Order By: Relevance
“…Nevertheless, although the discrepancy between biomarker data indicating recent sexual activity and self-reported sexual behavior has been reported previously, 36 this is the first time a validation study comparing biomarker outcomes with self-reported sexual behavior has been conducted within a study that also reported an increased HIV risk associated with injectable HC. Our results provide no evidence to support the hypothesis that differential over-reporting of condom use by HC users constitutes a primary explanation for the association between hormonal contraception use and HIV infection.…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, although the discrepancy between biomarker data indicating recent sexual activity and self-reported sexual behavior has been reported previously, 36 this is the first time a validation study comparing biomarker outcomes with self-reported sexual behavior has been conducted within a study that also reported an increased HIV risk associated with injectable HC. Our results provide no evidence to support the hypothesis that differential over-reporting of condom use by HC users constitutes a primary explanation for the association between hormonal contraception use and HIV infection.…”
Section: Discussionmentioning
confidence: 56%
“…Given these self-reports, we detected PSA in substantially fewer men than expected, especially compared to similar work in women (3). Low PSA levels prevented us from performing more sophisticated analyses of discordance (positive PSA despite report of no unprotected sex).…”
supporting
confidence: 44%
“…Valid measurement of sexual behaviors, including RAI, is critical for HIV prevention interventions. Yet, to date, nearly all sexual health research has relied on self-reported data, despite questionable validity (3, 4). Individuals may not accurately report whether, when, and how often they engage in risky behaviors, and research findings based on self-reported information may be biased.…”
mentioning
confidence: 99%
“…Most measures of condom use used in research rely on self-reported sexual behaviour rather than biomarkers, despite known inaccuracies in self-report. 1 Researchers may use questions about sexual behaviour as screening items for condom use questions and discard non-respondents from analysis. To decrease reliance on self-report, researchers have used semen exposure biomarkers in studies of HIV prevention 1 and recurrent bacterial vaginosis.…”
mentioning
confidence: 99%
“…1 Researchers may use questions about sexual behaviour as screening items for condom use questions and discard non-respondents from analysis. To decrease reliance on self-report, researchers have used semen exposure biomarkers in studies of HIV prevention 1 and recurrent bacterial vaginosis. 2 This study evaluated whether adolescent respondents who reported abstinence from vaginal sex would test negative for the semen Y-chromosome biomarker.…”
mentioning
confidence: 99%